Electronic properties in heterostructures under external fields (2022)
ABSTRACT: In this work, the electronic properties in various confinement geometries are analyzed for the study of systems such as quantum wells, quantum wires, and quantum dots based on materials such as GaAs, AlGaAs, InTe, among others. In the study carried out, the response of these systems to the action of external fields such as electric, magnetic and intense non-resonant laser fields is investigated. In addition to the study of the electronic properties in these systems, in the particular work related to 3D confinement, the hole states and with these, the excitonic contribution, and the modification of the properties by means of the inclusion of an impurity along the axis of symmetry of the system were studied. In the 2D confinement system, the electronic properties in quantum wires with various cross-sectional shapes were analyzed by means of a Self-Consistent Schrödinger-Poisson coupling, the emergence of Friedel-like oscillations in the electron density profile at low temperatures should be highlighted. Regarding one-dimensional systems, the electronic and optical response of a Razavy-like quantum well was analyzed with the inclusion of a doped delta layer, as well as the application of external magnetic and electric fields. Similarly, a finite semiconductor superlattice connected to two metal contacts was analyzed for the study of electron tunneling current, as well as the application of an external laser field for various geometric shapes. Finally, the electronic transport properties were studied again by means of the Self-Consistent method in double barrier tunneling systems with doping in the outer layers, these properties were calculated by means of the Landauer-Büttiker formalism and compared with experimental results of a Resonant Tunneling Diode based on InGaAs/AlAs.